Animal models of ischemic stroke and their impact on drug discovery. (4th March 2019) - Hermann, Dirk M.; Popa-Wagner, Aurel; Kleinschnitz, Christoph; Doeppner, Thorsten R.
ABSTRACT: Introduction : Representing the leading cause of long-term disability, ischemic stroke urgently needs further research and drug development. This review summarizes current animal models of ischemic stroke that can be used for drug discovery. Areas covered : Several reproducible models of permanent and transient focal cerebral ischemia have been established in a variety of animal species including rats and mice, in which a brain-supplying artery, often the middle cerebral artery, is occluded by mechanical devices including sutures, clips and hooks, pharmacological agents or delivery of blot clots. The authors review existing literature about these models, outlining their utility for evaluating acute and post-acute stroke treatments. Since stroke is an age-related disease that strongly affects humans with vascular risk factors and co-morbidities, the authors give focus to strategies replicating risk factors in ischemic stroke models. Furthermore, the authors present models of spontaneous stroke. Expert opinion : It is important that animal models mimic clinical conditions in a reliable and clinically relevant way, so here, they should replicate the pathophysiology of human stroke, stroke-associated risk factors and doses, times and modes of drug treatment. We propose that risk factor models should more widely be used in early drug discovery, if possible already during the identification of treatment targets.